Economic and emission dispatch using cuckoo search algorithm - Rachid Habachi; Abdellah Boulal; Achraf Touil; Abdelkabir Charkaoui; Abdelwahed Echchatbi (Institute of Advanced Engineering and Science, 2019)
The economic dispatch problem of power plays a very important role in the exploitation of electro-energy systems to judiciously distribute power generated by all plants. This paper proposes the use of Cuckoo Search Algorithm (CSA) for solving the economic and Emission dispatch. The effectiveness of the proposed approach has been tested on 3 generator system. CSA is a new meta-heuristic optimization method inspired from the obligate brood parasitism of some cuckoo species by laying their eggs in the nests of other host birds of other species.The results shows that performance of the proposed approach reveal the efficiently and robustness when compared results of other optimization algorithms reported in literature